Lovely beasts : the surprising truth [book with audioplayer] - Gardner, Kate (Kate Gardner Burt) (VOX books, 2019)
Spiders are creepy. Porcupines are scary. Bats are ugly. Or are they ... This captivating book invites you to learn more about awe-inspiring animals in the wild. After all, it's best not to judge a beast until you understand its full, lovely life.